ART OF TRADIONAL JEWELRY OF BUKHARA CREATION OF ALISHER HAYDAROV (Web of Teachers: Inderscience Research, 2024)
This article is about the art of jewelry which was revived after the independence of Uzbekistan. It gave a chance to use precious metal materials. The creative masters are working mainly in 2 directions: local jewelry (revival of forgotten traditions) and creating jewelry in a traditional and modern style. "Uch Kozacha", "Oy Baldoq", "Yr Bidor", "Kashkarboldoq" and others were created from traditional jewelry - amulets, charms. Among the masters the Dadamuhamedov dynasty, G. Yoldosheva, R. Mukhametshin, M. Nozirkhanov, Sh. Nizomov, I. Olimov, G. Tosheva and others carried out a number of works on the study, development and discovery of new trends in jewelry traditions. Some lines of Bukhara, Khorezm, Surkhandarya and other jewelry schools are combined to create new modern jewelry. "Ayol" (1998), "Africa" (1999), "Fish" (1999) by A. Ulumbekova; The works of E. Gostev "Flight" (1998), creative examples of R. Mukhametshin ("Tree of Life", 1993; Bracelets: snake-shaped bracelet (Bactria, 3rd century BC); watch bracelet (20th century). "Toghirmog" i", 2001) were distinguished by the decoration, subtlety of image, and creation based on classic examples of folk art. Currently, in addition to master jewelers, several associations - "Fonon" and "Kumush" association, "Nur" state jewelry center, "Musavvir" and "Ustazada" also fill the domestic market with jewelry.